Inferior Cubital Artery Perforator Flap for Soft-Tissue Coverage of the Elbow: Anatomical Study and Clinical Application. (16th March 2016) - Camuzard, Olivier; Foissac, Rémi; Clerico, Cyril; Fernandez, Jonathan; Balaguer, Thierry; Ihrai, Tarik; de Peretti, Fernand; Baqué, Patrick; Boileau, Pascal; Georgiou, Charalambos; Bronsard, Nicolas
Abstract : Background: Soft-tissue defects surrounding the elbow can be a challenging problem for the orthopaedic surgeon. Reliable reconstruction with use of muscular flaps or even perforator flaps derived from the surrounding vessels has been described. The inferior cubital artery (ICA) is an indirect septocutaneous perforator branch that most frequently arises from the lateral side of the radial artery. The purposes of the present study were to characterize the capillary cutaneous perforators of the ICA and to evaluate the potential of a local perforator flap procedure for soft-tissue coverage of the elbow. Methods: Twenty fresh cadaveric forearms were dissected in order to describe the ICA anatomy, and in ten additional forearms the ICA was selectively injected with a red ink solution to detail the ICA vascular territory. For each artery, we recorded the site of origin, the diameter of the artery at its source, the course of the artery, and the number, type, and diameter of capillary cutaneous perforators. Results: A total of seventy-eight ICA capillary perforators were analyzed from the twenty dissected forearms: forty-six were in-transit capillary perforators, nineteen were terminal capillary perforators, and thirteen were musculocutaneous capillary perforators. Of these seventy-eight perforators, sixteen (21%) had a caliber of <0.5 mm and sixty-two capillary perforators (79%) had a caliber of ≥0.5 mm. Ten ICAs were selectively injected, and the mean size of all stained skin areas was 30.9 ± 11.9 cm 2 . A perforator pedicled flap was readily feasible for all dissections. We also describe the case of a patient with a medial soft-tissue defect of the elbow that was covered with a pedicled perforator flap based on an ICA. The patient had satisfactory healing at two months. Conclusions: The ICA flap is a reliable and useful flap for elbow soft-tissue reconstruction. Clinical Relevance: The perforator flap procedure is a major advancement in reconstructive surgery. One potential application of the perforator flaps is the use of tissue adjacent to a defect as a perforator-based island flap. The use of this tissue allows for thinner flaps to be tailored for more accurate reconstruction. A flap that depends on a perforator branch of the radial artery called the inferior cubital artery seems to be an excellent solution for soft-tissue coverage of the elbow.